The gut microbiota protein BOC1 exhibits immune checkpoint inhibitor-like activity by inhibiting myeloid-derived suppressor cell differentiation - Bardouillet, Laureen; Orsini Delgado, Maria Lucia; Matondo, Caroline; Strozzi, Francesco; Thomas, Valentine; Chene, Laurent; Cultrone, Antonietta (Frontiers in Immunology, 2025)
BackgroundAdvancing research in oncology highlights the inverse correlation between antibiotic treatment and the positive outcomes of immune checkpoint inhibitor (ICI) administration, confirming once more the importance of microbiota and microbiota-derived compounds as complementary tools for treating cancer. Among the immune checkpoints, the CD200 cell surface glycoprotein has gained attention for its role in promoting self-tolerance and potentially facilitating tumor growth through interaction with the CD200R1 receptor.MethodsWe developed a robust AlphaLISA-based screening to identify human gut microbiota-derived proteins that may interact with CD200R1 and screened a library of 10,966 gut bacterial proteins. The antitumor activity of BOC1 was investigated in vitro by cytokine analysis, mixed lymphocyte reactions, and myeloid-derived suppressor cell (MDSC)–T-cell suppression assay. AlphaFold modeling was used to predict potential interaction points between BOC1 and CD200R1.ResultsWe successfully identified BOC1, a protein from the Bacteroides genus, showing better affinity than the natural ligand, CD200, toward the CD200R1 receptor. BOC1 induces cytokine secretion by monocyte-derived dendritic cells (MoDCs) and enhances CD8+/CD4+ T-cell populations and IFNγ production, highlighting its potent immunostimulatory properties. BOC1 also negatively impacts the differentiation of MDSCs, maintaining an immature monocytic profile (high CD14 and HLA-DR expression) and restoring T-cell proliferation even at low (10 nM) concentration. Mutation of amino acids within the N-terminal region of BOC1 reduces binding to CD200R1, supporting the importance of this region for a possible interaction with CD200R1.ConclusionThe immunostimulatory properties of BOC1 observed in vitro are compatible with an ICI-like behavior of this bacterial protein. Given that neither the CD200 protein nor the anti-CD200 antibody is able to compete with BOC1 for binding to CD200R1, and as supported by AlphaFold modeling predictions, CD200 and BOC1 might target different regions of CD200R1.